Defectos refractivos y su corrección quirúrgica (2009)
Refractive errors are very common on general population, signifcantly affecting quality of Ufe of patients. Currently there are several surgical alternatives for correction of these ametropias in the área of ophthalmology known as refractive surgery. One of the most used are photorefractive procedures with excimer láser. However when those errors have extreme magnitude, others approaches must be used like phakic infraocular lenses or phacoemulsifcation and infraocular lens implantation with refractive purposes. In this paper, using MEDLINE and searching in textbooks, a review was performed about historical issues, physiological optics, presumed ethiology and epidemiology of myopia, hyperopia and astigmatism and their surgical correction, and an overview of the current clinical and research status of the refractive surgery is provided. Moreover the current surgical criteria of Centro Oftalmológico Virgilio Galvis in refractive surgery are shown.   Key words: Refractive errors. Ametropias. Myopia. Hyperopia. Astigmatism. Excimer. Láser. Refractive surgery. Phakic infraocular lenses.